2017
DOI: 10.1007/s00300-017-2159-3
|View full text |Cite
|
Sign up to set email alerts
|

Species pool structure explains patterns of Antarctic rock-encrusting organism recruitment

Abstract: Understanding the population dynamics of benthic communities is impossible without understanding the processes related to their initial development, including recruitment. In polar areas, encrusting organisms, such as bryozoans, polychaetes, sponges and ascidians, are amongst some of the most species-rich and abundant groups of macrofaunal organisms, yet knowledge about their ecology is far from being complete. In this study, by investigating established encrusting assemblages and recruitment onto experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Such local differences in biodiversity is in good accord to the findings of Meyer et al (2017), who reported a high spatial and temporal variability in recruitment of hard‐ground communities. At sites with a high local species pool, more species can be observed on experimental substrates (Kuklinski et al, 2017). Given the very similar species richness found at 46 and 127 m water depth, our data does not support the observation of an exponential decrease in species richness with water depth, as reported by Meyer et al (2017) for depths between 7 and 215 m. In any case, the high overall species richness recorded by the Mosselbukta experiment clearly underlines the conclusion put forth already by Barnes & Kuklinski (2005) in that Arctic colonisation is slow but it is not poor in species.…”
Section: Resultsmentioning
confidence: 99%
“…Such local differences in biodiversity is in good accord to the findings of Meyer et al (2017), who reported a high spatial and temporal variability in recruitment of hard‐ground communities. At sites with a high local species pool, more species can be observed on experimental substrates (Kuklinski et al, 2017). Given the very similar species richness found at 46 and 127 m water depth, our data does not support the observation of an exponential decrease in species richness with water depth, as reported by Meyer et al (2017) for depths between 7 and 215 m. In any case, the high overall species richness recorded by the Mosselbukta experiment clearly underlines the conclusion put forth already by Barnes & Kuklinski (2005) in that Arctic colonisation is slow but it is not poor in species.…”
Section: Resultsmentioning
confidence: 99%